ELEMEN STRUKTUR BANGUNAN MESJID â€œSAKA TUNGGALâ€ BAITUSSALAM DI CIKAKAK, WANGON, BANYUMAS - YOHANA NURSRUWENING; WITA WIDYANDINI (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2015)
ABSTRACTIn an effort to get close to the real problems of the building of this research istaking an object on Baitussalam mosque, located in the Cikakak Village,Wangon, Banyumas. This mosque has a uniqueness that is not owned by anothermosque, which is constructed by using only one pole (saka) of wood, which bearthe entire burden of the mosque, that’s way the mosque is known as the "SakaTunggal" Mosque Cikakak. Is the structural elements in Baitussalam Mosque hasbeen able to respond the tropical climate in Banyumas, and to what extenttropical building’s technology can be applied to the Baitussalam Mosque inCikakak, Banyumas. Therefore, conducted research to determine the structuralanalysis of the mosque in the village Baitussalam Cikakak, Wangon, Banyumas.This research used a qualitative rationalistic method, and the method of analysisused descriptive qualitative method. Based on the analysis, we concluded that theBaitussalam Mosque in Cikakak, Banyumas is the Spiritual Architecture’sbuilding which structural elements used the combine of some traditional andmodern elements, so that resulted the transplantatip expression.Key words : Element structure, Building, Saka Tunggal, Cikakak Mosque